The Levy Institute Measure of Economic Well-Being: Estimates for Canada, 1999 and 2005 - Andrew Sharpe; Alexander Murray; Benjamin Evans; Elspeth Hazell (Levy Economics Institute of Bard College, 2011)
This report presents estimates of the Levy Institute Measure of Economic Well-Being (LIMEW) for a representative sample of Canadian households in 1999 and 2005. The results indicate that there was only modest growth in the average Canadian household's total command over economic resources in the six years between 1999 and 2005. Although inequality in economic well-being increased slightly over the 1999-2005 period, the LIMEW was more equally distributed across Canadian households than more common income measures (such as after-tax income) in both 1999 and 2005. The median household's economic well-being was lower in Canada than in the United States in both years.
Keywords: D13; D31; D63; 330; well-being; inequality; income; wealth; government expenditure; household production; LIMEW; Canada